Liver abscess effects on carcass performance and heritability estimates of liver abscess incidence and severity in beef on dairy heifers - Zuvich, Miranda Lee, author; Enns, R. Mark, advisor; Speidel, Scott E., advisor; Woerner, Dale, committee member; Holt, Timothy N., committee member (Colorado State University. Libraries, 2024)
The economic impact of liver abscesses has been reported to be not only due to loss from condemnation of livers but also from impacts on performance. A primary focus in decreasing liver abscess prevalence has been on prevention methods because with limited or no clinical signs present, diagnosis of liver abscesses in live animals is complicated, and no prevention methods have been highly effective in mitigation. As a result, this study aimed to identify the impacts of liver abscesses on carcass performance and estimate heritability for liver abscess incidence and severity in fed beef on dairy heifers. In the first study, 1,860 beef on dairy heifers were fed and harvested in Kansas. All had phenotypes for hot carcass weight (HCW; kg), rib eye area (REA; cm2), fat thickness (FT; cm), marbling score (MS), calculated visual yield grade (VYG), and liver abscess score. Of the 1,860 individuals, 1,646 had phenotypes for heart score (HS). Carcass impacts were estimated using fixed effects of liver abscess score, contemporary group, and age in days. The contemporary group was a concatenation of kill lot and treatment. Liver abscess score was fit in two different forms: 6 scores ("0", "A-", "A", "A+", "A+AD", "A+O") and 4 scores ("0", "A-", "A", "A+") where "A+" included scores of "A+AD" and "A+O". A score of "0" indicated no abscess and abscess severity increases with "A-", "A", and "A+". The scores of "A+AD", and "A+O" indicate there is adhesion of the liver to nearby organs and ruptured abscess, respectively. A significant increase was identified using the six-score model for FT for animals with scores of "A+O" compared to "A+", with respective least-squares means of 1.94 cm ± 0.12 and 1.59 cm ± 0.06 (P < 0.05). While not significant, tendencies were identified for FT for animals with scores of "A" and "A+AD" compared to "A+O" (0.05 ≤ P < 0.1) with respective least-squares means of 1.61 cm ± 0.06, 1.61 cm ± 0.05, and 1.94 cm ± 0.12. A significant increase was identified using the six-score model for VYG in animals with VYG scores of "A+O" higher than "A+" and "A+AD", with respective least-squares means of 3.75 ± 0.19, 3.20 ± 0.09, and 3.20 ± 0.08 (P < 0.05). When using the 4-score system, HCW was significantly lower for animals with scores of "A+" compared to those with non-abscessed livers. Hot carcass weight least-squares means for animals with no abscesses was 396 kg ± 2.63, and for those with severe abscesses was 391 kg ± 2.92 (P < 0.05). In the second study, 1,492 beef on dairy heifers fed and harvested in Kansas had liver abscess scores and sire information. Nine models were utilized to estimate heritability, all with fixed effects of contemporary group, age in days, and number of bovine respiratory disease treatments. The contemporary group was a concatenation of kill lot and treatment. Models 1, 4, and 7 were from data sets with all sires represented but had liver abscess score represented as a continuous variable, a binary score indicating abscess presence, and a binary score indicating severe abscess ("A+") presence, respectively. Models 2, 5, and 8 followed the same respective scoring systems as Models 1, 4, and 7, but the data set only included heifers from sires with 10 or more progeny. Models 3, 6, and 9 followed the same respective scoring systems as Models 1, 4, and 7, but the data set only included heifers from sires with 100 to 200 progeny in the complete data set. Heritability estimates from a sire model for Models 1, 4, and 7 ranged from 4.26 x 10-8 to 1.06 x 10-7. Heritability estimates from a sire model for Models 2, 5, and 8 ranged from 4.90 x 10-8 to 4.61 x 10-7. Heritability estimates from a sire model for Models 3, 6, and 9 ranged from 1.01 x 10-7 to 2.88 x 10-3. All estimates indicate no genetic component to liver abscess severity or incidence in this data set.
Keywords: beef on dairy; liver abscess; beef cattle; liver abscess heritability; carcass performance